Exploring traditional mongolian materia medica: the path of progress from tradition to modernity - Shi, Ruyu; Wang, Enironggui; Wang, Mengyang; Zhang, Chunhong; Damda, Tsend-Ayush; Li, Minhui (Frontiers in Pharmacology, 2025)
Traditional Mongolian medicine boasts a long history with its integrated and unigue theoretical system. Traditional Mongolian materia medica (TMMM), as the primary substance for the treatments in traditional Mongolian medicine, was thought to be an important source for drug discovery. Although interest in TMMM has recently grown among researchers, challenges of TMMM revitalisation should be concerned: (1) inheritors and sustainability, (2) effective composition and pharmacology, and (3) preparation and standardization. The purpose of the review is to introduce the current development of Mongolian medicine and summarize the future challenges to make better use of Mongolian medicine.